Irrigation Scheduling in Crop Management System - Salgado, Eduardo (2019)
Center pivor systems are widely used to suppress the irrigation needs of agricultural fields. In this article, we propose an autonomous to improve the low efficiency of this method of irrigation, developing a system based on the water requirement of the plantation, through field data (local temperature, local wind, soil moisture and precipitation forecast) and soil evapotranspiration calculation. The stored information will allow to calculatem the real evapotranspiration, not being necessary to restrict to lysometric measures. Accordingly, it is possible to schedule the irrigation for the period in which it has the lowest cost, considering the energy produced locally and the price of energy bought in the main market. Irrigation must be carried out within the time interval in which the plantation does not reach the wilding point, so it will be carried out at the time of the lowest cost.